Emotions and community development after return migration in the rural Arctic - Aure, Marit; Riabova, Larissa (Taylor & Francis, 2020)
Source at https://doi.org/10.4324/9781003022367. Migration is emotive, evoking feelings of hopelessness, fear, or optimism for human and economic development, yet the role of emotions in post-migration community development gains limited attention. This chapter discusses the role of emotions in migration and rural development after the return of migrants, drawing on studies of temporary labour migration from Teriberka, a small coastal village in the Russian Arctic, to Båtsfjord, a small fishing community in Norway. The materials include community studies in these places 20 years ago, when the migration started, and several follow-up studies. Norwegian and Russian businessmen organised the migration for work in the fish-processing industry, and the project ceased after three years. Most actors expected that the migration would improve the migrants’ economic situation and spur development in the home community. This chapter argues that emotions play a significant role in expectations and considerations before and during migration, and help explain the lack of development in the community of origin after migration ended and migrants returned. Migrants used their migration experiences in post-return individual strategies, but to a lesser degree at the community level. Positive emotional capital obtained during the residency in Norway was depleted by negative emotions related to public policies after the migrants’ return.